Citra Allah: Antara Kami dan Mereka - Semy Arayunedya (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2023)
A Christian's acknowledgment that God's image is also found in others is a Christian political hospitality. Because it is political, Christian hospitality does not promote the mentality of us and those where we are identified as victims and those who are labeled oppressors. Many scholars have identified this mentality as the root cause of various social pathologies such as colonialism, war, to identity politics which political demagogues and buzzers have amplified. Our problem may not lie in our ability to differentiate between us and them because this mentality is inherent. However, we—as the image of God—may have failed, first and foremost, to love.